Abundances and indices for soil microbial biomarkers (brGDGTs and isoGDGTs) in eleven soil profiles along a Serengeti transect - Peaple, Mark D; Feakins, Sarah J; Tierney, Jessica E; Levin, Naomi E; Häggi, Christoph; Beverly, Emily J; Baker, Samantha; Garza, Brittany (PANGAEA, 2022)
Soil profiles were collected along a transect across the Serengeti ecosystem, in Tanzania from 2-3S and 34-35.5E, 1153 to 1677 m above sea level and 0 to 1.6 m soil depth. The samples are modern soils and the temporal span of the soil depth profiles is unconstrained, likely centuries to millennia. The survey is intended to observe soil microbial lipid biomarkers that are commonly used as proxies for temperature and pH and to assess their robustness in alkaline carbonate-precipitating soil profiles, where soil carbonate proxies can also be applied. These modern calibrations can inform reconstructions of Eastern African paleoenvironments using the same proxies in geological archives. Lipid extractions and purifications were performed at USC in 2018-2019 and abundances of branched and isoprenoidal glycerol dialkyl glycerol tetraethers were obtained by high pressure liquid chromatography mass spectrometry, performed in 2020-2021 at the University of Arizona. Contextual data include total dissolved solids and pH measurements at the University of Houston in 2020-2021. For more information, please consult associated manuscript on the GDGTs within these soil profiles: Peaple et al., (2022) Identifying the drivers of GDGT distributions in alkaline soil profiles within the Serengeti ecosystem, Organic Geochemistry, in review. A publication on the bulk organics and compound specific carbon isotopic composition of plant waxes in the same soils: Zhang, et al. (2021) Carbon isotopic composition of plant waxes, bulk organics and carbonates from soils of the Serengeti grasslands, Geochimica et Cosmochimica Acta, 311, 316-331, doi:10.1016/j.gca.2021.07.005. That study includes stable hydrogen isotopic data on plant wax, available from doi:10.1594/PANGAEA.921002. A publication on multiple oxygen isotopes within carbonates in the same soil profiles can be found at: Beverly, E.J., Levin, N.E., Passey, B.H., Aron, P.G., Yarian, D.A., Page, M. and Pelletier, E.M. (2021) Triple oxygen and clumped isotopes in modern soil carbonate along an aridity gradient in the Serengeti, Tanzania. Earth and Planetary Science Letters, 567, 116952, doi:10.1016/j.epsl.2021.116952. That study includes stable carbon isotopic data on soil carbonates, available from doi:10.5281/zenodo.4919027.
Keywords: GDGTs; pH; Salinity; Soil